Treating spinal cord injury in rats with a combination of human fetal neural stem cells and hydrogels modified with serotonin - Růžička, Jiří; Romanyuk, Nataliya; Hejčl, Aleš; Vetrík, Miroslav; Hrubý, Martin; Cocks, Graham; Cihlár, Jiří; Přádný, Martin; Price, Jack; Syková, Eva; Jendelová, Pavla (Acta neurobiologiae experimentalis, 2013)
Currently, there is no effective strategy for the treatment of spinal cord injury (SCI). A combination of biomaterials and stem cell therapy seems to be a promising approach to increase regenerative potential after SCI. We evaluated the use of a cellpolymer construct based on a combination of the conditionally immortalized spinal progenitor cell line SPC-01_GFP3, derived from human fetal spinal cord tissue, with a serotonin-modified poly(2-hydroxyethyl methacrylate) hydrogel (pHEMA-5HT). We compared the effect of treatment with a pHEMA-5HT hydrogel seeded with SPC-01_GFP3 cells, treatment with a pHEMA-5HT only and no treatment on functional outcome and tissue reconstruction in hemisected rats. Prior to transplantation the cell-polymer construct displayed a high potential to support the growth, proliferation and differentiation of SPC-01 cells in vitro. One month after surgery, combined hydrogel-cell treatment reduced astrogliosis and tissue atrophy and increased axonal and blood vessel ingrowth into the implant; however, two months later only the ingrowth of blood vessels remained increased. SPC-01_GFP3 cells survived well in vivo and expressed advanced markers of neuronal differentiation. However, a majority of the transplanted cells migrated out of the lesion and only rarely remained in the hydrogel. No differences among the groups in motor or sensory recovery were observed. Despite the support of the hydrogel as a cell carrier in vitro, and good results in vivo one month postsurgery, there was only a small effect on long term recovery, mainly due to the limited ability of the hydrogels to support the in vivo growth and differentiation of cells within the implant. Further modifications will be necessary to achieve stable long term improvement in functional outcome.
Keywords: transfekce; modely nemocí na zvířatech; myelinové proteiny; jizva; Male; Rats, Wistar; Fetal Stem Cells; Cell Proliferation; Transfection; atrofie; Cholinesterases; serotonin; buněčná diferenciace; proteiny nervové tkáně; mužské pohlaví; potkani Wistar; transplantace kmenových buněk; lokomoce; krysa rodu Rattus; Atrophy; zelené fluorescenční proteiny; Animals; Locomotion; lidé; PEG-DMA hydrogel; Neural Stem Cells; Spinal Cord Injuries; Stem Cell Transplantation; Humans; poranění míchy; zvířata; Hydrogel, Polyethylene Glycol Dimethacrylate; Rats; Disease Models, Animal; Green Fluorescent Proteins; proliferace buněk; cholinesterasy; nervové kmenové buňky; fetální kmenové buňky; Myelin Proteins; Serotonin; Nerve Tissue Proteins; Cell Differentiation; Cicatrix